The design, synthesis and biological evaluation of novel URB602 analogues as potential monoacylglycerol lipase inhibitors - Szabo, M.; Agostino, Mark; Malone, D.; Yuriev, E.; Capuano, B. (Pergamon, 2011)
We have synthesised an extensive series of URB602 analogues as inhibitors of monoacylglycerol lipase (MAGL), which is the major enzyme responsible for metabolising the endocannabinoid 2-arachidonylglycerol. The recently identified crystal structure of MAGL was used in the design strategy and revealed three possible binding sites for URB602 and the proposed analogues. A test series of carbamate analogues were docked into the identified sites to predict the most favourable binding location. The synthesised analogues of URB602 explored the biological effects of isosteric replacement, ring size and substitution, para substitution of the biphenyl moiety and the incorporation of a bicyclic element. The compounds were tested for their ability to inhibit human MAGL. The carbamate analogue 16 displayed the most significant inhibitory activity, reducing MAGL activity to 26% of controls at 100 μM compared to 73% for the parent compound URB602.